Whose promises are worth more? How social status affects trust in promises. (5th June 2019) - Blue, Philip R.; Hu, Jie; Peng, Lu; Yu, Hongbo; Liu, Huiying; Zhou, Xiaolin
Abstract: Promises are among the most widely used tools for increasing trust in social hierarchies; yet the effect of social status on trust in promises is unknown. Here we used a modified version of the Trust Game, in which participants, acting as Investors, were paired with Trustees of varying social status who were given the opportunity to promise (or not) to return at least half of the multiplied amount (i.e., 4 × the amount invested). No return feedback was provided. Participants invested more in partners who promised than those who did not or whose promise information was concealed. Importantly, in both lab‐manipulated (Exps. 1–3: math‐induced) and pre‐existing (Exp. 4: university‐based) hierarchies, participants invested more in promises given by high status than low status partners. Post‐experiment measures suggest that this may be due to greater expectations of honesty for high status than low status others. Potential explanations and implications are discussed.